FISCAL BALANCE AND SUSTAINABLE ECONOMIC DEVELOPMENT IN NIGERIA - ODILI OKWUCHUKWU; OKORO KELECHI OKORO; NWANNEDIYA FAITH OTI-IBIAM (International Studies Journal)
This study analyzed the effects of fiscal balance on sustainable economic development in Nigeria from 1981 to 2022. Autoregressive Distributed Lag (ARDL) model was employed in estimating the variables. The ARDL results indicated that the relationship between fiscal balance and sustainable economic development followed a long-run path. The study found that fiscal balance to GDP ratio, external debt to export ratio, and public debt service to revenue ratio had negative impact on growth rate of real GDP per capita (GDPgr). Total debt stock to GDP ratio had positive effect on GDPgr. Domestic debt to domestic investments ratio and recurrent expenditure to GDP ratio exerted negative and non-significant effect on GDPgr. Debt for gross fixed capital formation as a percentage of GDPand trade openness exerted positive and significant effect on GDPgr. The study recommended that the government should focus on viable capital investments that have the potential to generate revenue that can service public debt in order not to create debt that are not sustainable. Government should take proactive measures to ensure that public debt is employed in key productive sectors of the economy to boost domestic production and enhance export receipts in foreign currency capable of repaying the externally borrowed funds. There is need for government to reduce recurrent expenditures since it does not lead directly to revenue generation, capital formation, savings and investment in such manner that it would increase economic assets, boost production, and promote sustainable economic development.